The Raven : tales and poems - Poe, Edgar Allan, 1809-1849 (Penguin horror., 2013)
Presents an anthology of works from the master of mystery and the macabre, including such pieces as "The Tell-Tale Heart," "The Masque of the Red Death," and a selection of poems.